Bebola: rule based expert system of young football player selection / Mohammad Sollehin Abd Halim - Abd Halim, Mohammad Sollehin (2020)
Football is one of the famous sport in the school and attract many young students to join the football team in school. However, selection of young player position is not easy as the student lack of knowledge about the position requirement for every specific position. The other problem is the unorganized traditional method to select a player because of traditional method basically used coach’s intuition during the selection that can be influence by unnecessary factor such as emotions. The objective of the project is to design a system which could make selection on young age football player and their position based on their skill play using rule base method. Next, to develop a rule base expert system of young football player selection based on four types of position. The third objective is to test the functionality and usability of the system. The project will implement the forward chain rule based in the expert system. The functionality and usability test has been conducted for the purpose of correctness of the system. From the testing, 4 from 5 of the student taking the test produces a same result as the position of the student in the school. The significance of the study is to help young age player to get a match position based on position skill in football. Other than that, the study can help football’s coach to make selection for the new player in football at young age.